The influence of aerobic exercise on extracellular vesicles in obesity - Hayward, Brittany, author; Lark, Dan, advisor; Bell, Christopher, committee member; LaRocca, Tom, committee member; Kruh-Garcia, Nicole, committee member (Colorado State University. Libraries, 2021)
Purpose: Cardiometabolic disease is the leading cause of death in the United States. Metabolic syndrome describes several common metabolic parameters that increase risk of developing cardiometabolic disease(s). However, current risk factors of metabolic syndrome laid out by the American Heart Association have a poor correlation to cardiometabolic disease development. Prevention of metabolic syndrome and by extension cardiometabolic disease is perhaps the best method to combat morbidity and mortality. Exercise is one intervention that has proved not only to decrease the chance of developing chronic disease, but also reverse symptoms of those already experiencing metabolic dysfunction. Therefore, exercise could be the most potent treatment of metabolic syndrome and by extension cardiometabolic diseases. However, since exercise is a multisystemic and highly integrative stimulus, the mechanisms responsible for the beneficial adaptations of exercise are not yet fully understood. Extracellular vesicles are a heterogeneous subclass of excreted biologically active molecules that function to facilitate cell-to-cell communication. Extracellular vesicles are released during cardiometabolic disease and in response to exercise, but their relationship to metabolic health is poorly understood. Therefore, our objective was to examine if aerobic exercise alters the plasma concentration and/or size of circulating extracellular vesicles during both an acute bout of exercise and from exercise training. We then examined the relationship between extracellular vesicle plasma concentration and our subject's characteristics such as age, sex, body mass index, percent fat mass, peak oxygen consumption, among other physiological characteristics. Methods and Results: This study utilized plasma samples from subjects recruited from a recent clinical trial. Sedentary, overweight, but otherwise healthy men and women were invited to participate in a SGLT2 inhibitor exercise study. Thirty adults were recruited, fifteen adults were given an SGLT2 inhibitor and fifteen were on a placebo. Here, we examined only placebo treated subjects (N=14; 6/8 M/F; 23 ± 8 y; 30.6 ± 3.8 kg/m2; mean ± SD). Subjects underwent several baseline tests including maximal and submaximal exercise tests and body composition analysis. The subjects then participated in twelve weeks of a supervised aerobic exercise intervention. The baseline tests were repeated immediately after the intervention. Blood samples were taken during the submaximal standardized exercise test that was conducted before and after the exercise intervention. Extracellular vesicles were isolated and analyzed for their concentration and size distribution using nanoparticle tracking analysis. After excluding severely hemolyzed samples, six subjects were included in the extracellular vesicle analysis (3/3 M/F; 28 ± 11 y; 30.7 ± 3.4 kg/m2; mean ± SD). Our results indicate that the acute standardized exercise bout did not elicit changes in the concentration nor the size of extracellular vesicles. Additionally, when comparing samples pre- and post-exercise training, there was no change in extracellular vesicle concentration nor size. Collectively, these data insinuate an acute bout of submaximal exercise and/or exercise training do not increase circulating extracellular vesicle concentration in sedentary obese individuals. Linear regressions were performed, and Pearson correlation coefficients were reported in order to examine relationships between EV concentration and physiological factors. BMI, fat mass, percent body fat, lean mass, and oxygen consumption correlated with EV concentration in samples that were low to moderately hemolyzed (absorption <0.3 at 414 nm). However, the sample size was small and further investigations are needed. Conclusion: This study did not find any changes in extracellular vesicle concentration/size in untrained or trained subjects. However, several correlations between extracellular vesicle concentration and subject characteristics were found in sedentary and trained overweight but otherwise healthy adults. This study had several limitations that could have restricted our results, and therefore additional research is warranted to understand the connection between exercise and circulating extracellular vesicle characteristics.
Keywords: extracellular vesicles; exercise; obesity